1989
DOI: 10.1002/bem.2250100307
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure of primates to 60‐Hz electric and magnetic fields: II. Neurochemical effects

Abstract: We exposed Macaca nemestrina (pig-tailed macaques) to electric (E) and magnetic (B) fields ranging in intensity from 3 kV/m and 0.1 G to 30 kV/m and 0.9 G for three 21-day (d) periods. Experimental animals were exposed to sham E and B fields for two 21-d periods, one prior to and one following actual exposure to E and B fields, resulting in a total of five 21-d periods. Control animals were exposed to sham E and B fields for the entire 105-d interval. At the end of each 21-d period cerebrospinal fluid (CSF) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 26 publications
0
12
1
Order By: Relevance
“…studies have not confirmed these results [Peters et al, 1991;Feychting and Ahlbom, 1993;Olsen et al, 1993; *Correspondence to: Luigi Zecca, Institute of Advanced Biomedical Technologies C.N.R., Via Ampere 56, 20131 Milan, Italy. system (acetylcholine, dopamine, serotonin, amino 26.5 cm long, 30 cm high polycarbonate cages. These were placed on electrically grounded metal nets and acids), and protein content in the brain of animals exposed to EMF [Vasquez et al, 1988;Seegal et al, placed in three identical exposure units. The electric field was generated by parallel electrodes with a 40 cm 1989; Zecca et al, 1991;Hagino et al, 1992;Lai et al, 1993;Yu et al, 1993].…”
Section: Introductionmentioning
confidence: 99%
“…studies have not confirmed these results [Peters et al, 1991;Feychting and Ahlbom, 1993;Olsen et al, 1993; *Correspondence to: Luigi Zecca, Institute of Advanced Biomedical Technologies C.N.R., Via Ampere 56, 20131 Milan, Italy. system (acetylcholine, dopamine, serotonin, amino 26.5 cm long, 30 cm high polycarbonate cages. These were placed on electrically grounded metal nets and acids), and protein content in the brain of animals exposed to EMF [Vasquez et al, 1988;Seegal et al, placed in three identical exposure units. The electric field was generated by parallel electrodes with a 40 cm 1989; Zecca et al, 1991;Hagino et al, 1992;Lai et al, 1993;Yu et al, 1993].…”
Section: Introductionmentioning
confidence: 99%
“…Further work on the effects of MF on 5-HT 1B receptor binding will include the use of another specific agonist, [ It is unclear how our data relate to changes in vivo, but some published results suggest that exposure to ELF EMF can modulate 5-HT metabolism in the brain [Seegal et al, 1989;Canedo et al, 2003;Sieron et al, 2004].…”
Section: Mechanismmentioning
confidence: 88%
“…Wolpaw et al [1989], Seegal et al [1989], and Dowman et al [1989] studied the effects of 60 Hz E/ MF on a number of neurophysiologic endpoints in young, juvenile pigtail macaques (Macaca nemestrina). These researchers exposed the subjects to three 21 day exposure segments of differing field intensity (3 kV/ m, 10 pT; 10 kV/m, 30 pT; and 30 kV/m, 90 pT).…”
Section: Other Primate Studiesmentioning
confidence: 99%